(untitled) (Bangladesh Journal of Anatomy, 2009)
Objective: In ‘Curriculum’ 2002 short answer questions are newly introduced. The content of 1st professional written examination was given but the weightage of different subdivision of Anatomy is not mentioned. So, present study was done to see the content validity of different subdivisions of Anatomy in written examinations. Study design: Descriptive type of study Place and period of study: The study was carried out from January 2003 to July 2004 in the Department of Anatomy, Bangabandhu Skeikh Mujib Medical University, Dhaka. Methods: It was based on a quantitative method; the question paper analysis based study. Results: It is evident from the questions paper analysis that different subdivisions of Anatomy are usually not given proper weight in the Anatomy written examinations. There are some subdivisions of Anatomy which are usually covered less than required. These include Genetics, Histology, General Anatomy, General Developmental Anatomy, Clinical Anatomy, etc. Conclusion: for further improvement of assessment system of Anatomy, content validity is needed to be established. Key words: Content validity, Anatomy, undergraduate, written examinations doi: 10.3329/bja.v7i1.3011 Bangladesh Journal of Anatomy January 2009, Vol. 7 No. 1 pp. 14-18